Mapping of Posphorus, Potassium, and C-organic Nutrient Status of Dry Land Using Dry Soil Testing Equipment (PUTK) in Pamulihan Dystrict Sumedang Regency - Sondari, Nunung; Suryaman, Suryaman; Amalia, Lia; Turmuktini, Tien; Parlinah, Linlin; Nurlukman, Candra Perkasa; Ulfah, Indriana; Samsu, Asep (Jurnal Agrosci, 2025)
This study aims to determine the status of P, K, and C-Organic nutrients in the dry land soil of Pamulihan Dystrictt, Sumedang Regency. The study was conducted to map the status of P, K, and C-Organic nutrients in the dry land of Pamulihan Dystrictt according to the guidelines for using the Dry Land Soil Test Kit (PUTK). The research was carried out from July 2024 to August 2024 in Pamulihan Dystrictt. The research method involved collecting primary data through field surveys, determining the number and location of sample points using random sampling with the ArcGIS 10.8 application, collecting samples at the designated points, and analyzing the chemical properties of the dry land soil in Pamulihan Dystrictt according to the guidelines for using the Dry Land Soil Test Kit (PUTK). Geographic data were collected and analyzed using GIS technology to map the status of P, K, and C-Organic nutrients in the dry land of Pamulihan Dystrictt. The results of the nutrient status testing in the dry land of Pamulihan Dystrictt, particularly in the villages of Cigendel, Citali, Haurngombong, Pamulihan, and Sukawangi, showed low, medium, and high phosphorus (P) levels, predominantly low with an area of 216.29 ha (55%). Potassium (K) testing showed medium and high levels, predominantly medium with an area of 246.14 ha (62.61%). C-Organic testing showed low levels across an area of 393.13 ha (100%). Fertilization recommendations for crops were made based on the nutrient needs of each plant according to the fertilization recommendation guidelines in the Dry Land Soil Test Kit (PUTK). The conclusion of this study is that the nutrient status of dry land in Pamulihan Dystrictt shows low phosphorus (P), medium potassium (K), and low C-Organic levels. The mapping of P, K, and C-Organic nutrient status in the dry land of Pamulihan Dystrictt was done in a semi-detailed map with a scale of 1:50,000.